Etiology and bacterial sensibility in children urinary infection. Hospital Infantil Club Noel and Hospital Universitario del Valle, Cali, Colombia. (Colombia Medica, 2007)
Introduction: Urinary tract infection (UTI) is the most common renal disease in childhood. To find the etiologic microorganism and an early adequate antibiotic therapy are essential to avoid permanent kidney injuries. Objectives: To know the etiologic bacteria and their antibiotic sensibility in urine cultures of children with UTI consulting University Hospital and Club Noel Hospital in Cali, Colombia. Methodology: A total of 123 children under 14 years of age that came into Emergency Service or outpatient clinics at University Hospital or Club Noel Hospital with clinical suspicion of UTI from August 2004 to February 2005 were included in a descriptive transversal study. Urine cultures were taken by supra-pubic aspiration, urine catheterization or mid strain urine. UTI definition was based on colony counts according to recollection method. Positive urine cultures, type of bacteria and antibiotic sensibility were considered for the analysis. Children having either urine cultures with colony counts inferior to recollection method, asymptomatic bacteriuria, occasional catheterization, immunosuppression, vesicostomy or previous admission to intensive care unit, were excluded. Results: Among 123 children entering to the study, 31 were eliminated for colony counts inferior to the recollection method. A total of 123 urine cultures were left for the analysis: 50% of urine cultures were obtained by catheterization, 33% via mid void stream and 17% by supra-pubic aspiration; 58% of patients were females. Escherichia coli was cultured in 72% of the cases, Klebsiella in 16.4%, Proteus 2.5% and other type of bacteria account for 9%. Antibiotics and antibacterials with sensibility over 80% were: cefixime, norfloxocin, cefuroxime, cefprozil, nalidixic acid, ceftriaxone, amikacin, and gentamicin. Intermediate sensibility from 61 to 70%: amoxicillin-clavulinic, cefaclor, ciprofloxacin, and nitrofurantoin. Sensibility under 60% was found for amoxicillin, ampicillin, cefadroxil, cephalexin, cephradine, trimethoprim-sulfa, ampicillin–sulbactam, cephalothin and cefazolin. Conclusions: E. coli is the main cause of UTI in the pediatric population of Cali. Usual recommended antibiotic and antibacterial for UTI empiric therapy are cephalexin, trimethoprim-sulfa, ampicillin, and amoxicillin. In accordance with the results in the present study resistance of bacteria to these medicaments was high. Antibiotics and antibacterials with better sensitivity were: cefuroxime, cefproxil, cefixime and nalidixic acid which the authors recommend for empiric oral therapy while the urine culture is in process and final results arrive. In spite of norfloxocin good sensitivity, its use should be reserved for especial cases where resistance to other antibiotics is found. If there is an indication for intravenous treatment, ceftriaxone or amikacin are recommended.